Doxycycline-integrated silk fibroin hydrogel: preparation, characterizations, and antimicrobial assessment for biomedical applications - Kranti Kiran Reddy Ealla; Chandra Sri Durga; Vikas Sahu; Neema Kumari; Jayachandran Venkatesan; Vishnu Priya Veeraraghavan; Pratibha Ramani; Kiran Kumar Bokara; Karthikeyan Ramalingam (BMC Oral Health)
Abstract Background Tooth extraction, a common dental procedure, is often accompanied by pain, trismus, and swelling due to alveolitis caused by oral bacteria. Doxycycline is prescribed to alleviate infection and improve socket healing, but its immediate absorption in the bloodstream makes the treatment less effective at oral sites. This emphasizes the importance of a drug delivery system to gradually slow its release at the oral wound site and increase its bioavailability to make the treatment effective over time. Methods Silk fibroin (SF) - doxycycline hyclate (DH) hydrogel was developed and subsequently characterized for gelation kinetics, swelling, stress-strain analysis, morphology using scanning electron microscopy, interaction between SF and DH using Fourier transform infrared (FT-IR) spectroscopy, drug release profile, antibacterial efficacy, and biocompatibility studies. Results The results indicated that the SF-DH hydrogel maintained its structural integrity, tolerated stress and strain, and featured interconnected pores, confirming DH integration within the SF matrix. The SF-DH hydrogel formed within 8 h with the pore size range of 20–150 μm and 90.72 kPa Young’s modulus. The drug release profile showed the increased release of DH up to 2 h, followed by sustained release till 8 h. The zone of inhibition was smaller with SF-DH hydrogels compared with DH for both Staphylococcus aureus and Streptococcus mutans. Furthermore, MC3T3-E1 cells showed 90% viability with SF-DH hydrogel. Conclusions The findings suggest that SF-DH hydrogel showed sufficient mechanical strength, pore size, antimicrobial activity, and biocompatibility. Further in vivo and clinical tests are required to prove its efficacy in effective socket healing.